A Chance to Make Good : African Americans 1900-1929. - Grossman, James R. (Young Oxford History of African Americans Ser., 1997)
Currently we think of the first three decades of the 20th century as the formative years of Jim Crow. Yet in the face of legal discrimination a new generation of African Americans left an indelible mark on the nation and its affairs. A Chance to Make Good documents the rise of black businesses and political coalitions, and African American contributions to music and culture, and the efforts of individuals and communities to claim a place for themselves in America during the years 1900-1929. It was a time of movement, the Great Migration, when approximately 1.5 million African Americans left th.